RESTABELECIMENTO DE SISTEMAS DE DISTRIBUIÇÃO DE ENERGIA ATRAVÉS DA TÉCNICA ENXAME DE PARTÍCULAS - Willer Oliveira, Leonardo; Rocha Oliveira, Ângelo; Chaves Silva Junior, Ivo; Vanderson Gomes, Flávio; José Oliveira, Edimar (LINKSCIENCEPLACE, 2016)
This paper proposes an approach for the optimal restoration of radial electrical distribution systems after an incident. The complex problem requires a decision-making process whose combinatorial nature can avoid the assessment of all possible solutions within feasible computational times. Therefore, the proposed approach is based on the binary particle swarm optimization (PSO) for handling the discrete variables related to the switching decision. The restoration process comprises a multi-objective reconfiguration model in which the objectives are to maximize the supplied load and improve the voltage regulation, with minimum loss and switching maneuvers. A case study is performed to evaluate the proposed methodology.